Association between postnatal growth and neurodevelopmental impairment by sex at 2 years of corrected age in a multi-national cohort of very preterm children. Issue 8 (August 2021) - El Rafei, Rym; Jarreau, Pierre Henri; Norman, Mikael; Maier, Rolf Felix; Barros, Henrique; Van Reempts, Patrick; Pedersen, Pernille; Cuttini, Marina; Costa, Raquel; Zemlin, Michael; Draper, Elizabeth S.; Zeitlin, Jennifer; et al.
Summary: Background & aims: Extra-uterine growth restriction (EUGR) is common among very preterm (VPT) infants and has been associated with impaired neurodevelopment. Some research suggests that adverse effects of EUGR may be more severe in boys. We investigated EUGR and neurodevelopment at 2 years of corrected age (CA) by sex in a VPT birth cohort. Methods: Data come from a population-based cohort of children born <32 weeks' gestation from 11 European countries and followed up at 2 years CA. Postnatal growth during the neonatal hospitalization was measured with: (1) birthweight and discharge-weight Z-score differences using Fenton charts (2) weight-gain velocity using Patel's model. Published cut-offs were used to define EUGR as none, moderate or severe. Neurodevelopmental impairment was assessed using a parent-report questionnaire, with standardized questions/instruments on motor function, vision, hearing and non-verbal cognition. We estimated relative risks (RR) adjusting for maternal and neonatal characteristics overall and by sex. Results: Among 4197 infants, the prevalence of moderate to severe impairment at 2 years CA was 17.7%. Severe EUGR was associated with neurodevelopmental impairment in the overall sample and the interaction with sex was significant. For boys, adjusted RR were 1.57 (95% Confidence Intervals (CI): 1.18–2.09) for Fenton's delta Z-score and 1.50 (95% CI: 1.12–2.01) for Patel's weight-gain velocity, while for girls they were 0.97 (0.76–1.22) and 1.12 (0.90–1.40) respectively. Conclusion: EUGR was associated with poor neurodevelopment at 2 years among VPT boys but not girls. Understanding why boys are more susceptible to the effects of poor growth is needed to develop appropriate healthcare strategies.